A review of the European species of the genus Tetragoneura Winnertz (Diptera: Mycetophilidae) ALEXEI POLEVOI (Russia) & JEVGENI JAKOVLEV (Finland) - Polevoi, Alexei; Jakovlev, Jevgeni (Zootaxa, 2011)
Five European species of the genus Tetragoneura Winnertz (Diptera: Mycetophilidae) are reviewed. Male terminalia of all species as well as female terminalia of T. ambigua Grzegorzek, T. sylvatica Curtis and T. ruuhijarvi sp. n. are illustrated on the base of type and newly collected material. Two species: T. ruuhijarvi sp. n. and T. pudogensis sp. n. are described based on specimens collected in Finland and Russian Karelia. T. sibirica Maximova is found to be a junior synonym of T. obirata Plassmann. Key to European species is provided.